Early Life Stress and the Fate of Kynurenine Pathway Metabolites - Coplan, Jeremy D.; George, Roza; Syed, Shariful A.; Rozenboym, Annalam V.; Tang, Jean E.; Fulton, Sasha L.; Perera, Tarique D. (Frontiers in Human Neuroscience, 2021)
Early life stress (ELS) precedes adult inflammation which may mediate an increased risk for stress-related psychiatric disorders, potentially through alterations of central kynurenine pathway (KP) metabolites, the latter being relatively unexplored. We hypothesized that ELS in a nonhuman primate model would lead to reduction of neuroprotective and increases of neurotoxic KP metabolites. 12 adult female bonnet macaques reared under conditions of maternal variable foraging demand (VFD) were compared to 27 age- and weight-matched non-VFD exposed female controls. Baseline behavioral observations of social affiliation were taken over a 12-week period followed by the first cerebrospinal fluid (CSF) sample. Subjects were then exposed either to a 12-week repeated separation paradigm (RSP) or assigned to a “no-RSP” condition followed by a second CSF. We used high performance liquid chromatography for kynurenine (KYN), tryptophan, 5-hydroxyindole-acetic acid, kynurenic acid (KYNA), and anthranilic acid (ANTH) as a proxy for quinolinic acid determination. At baseline, social affiliation scores were reduced in VFD-reared versus control subjects. CSF log KYNA and log KYNA/KYN ratio were lower in VFD-reared versus control subjects. CSF log KYNA/KYN was positively correlated with CSF log ANTH in VFD only (r = 0.82). Controlling for log KYNA/KYN, log ANTH was elevated in VFD-reared subjects versus controls. CSF log KYNA/KYN obtained post-RSP was positively correlated with mean social affiliation scores during RSP, specifically in VFD. ELS is associated with reduced neuroprotective and an increase of neurotoxic pathway products. That the two contrasting processes are paradoxically correlated following ELS suggests cross-talk between two opposing KP enzymatic systems.